Depression among older adults in Malaysian daycare centres - Ong, Swee Leong; Ghazali, Suriawati; Hussin, Emni Omar Daw; Soh, Kim Lam; Japar, Salimah; Soh, Kim Geok; Mat Azmi, Intan Suhana (Mark Allen Group, 2020)
With the older population increasing worldwide, depressive disorder in this cohort is a serious public health problem that contributes to increased healthcare costs and mortality. This study aimed to determine the prevalence of depression among older adults in Malaysia who attended a daycare centre and to identify the relationship between depression and demographic factors. A cross-sectional study was conducted with 159 older adults recruited following screening for mental capacity. The Malay Geriatric Depression Scale questionnaire was distributed among the participants to obtain descriptive data on the symptoms of depression. Some 59.1% of the participants experienced depression. The most common factors associated with depression were being divorced, low education levels and low income. The findings indicate the need to revise and re-evaluate the activities and programmes in daycare centres for older adults in order to objectively cater to their physical and emotional needs.